Maternal smoking during pregnancy and long-term ophthalmic morbidity of the offspring. (December 2021) - Tsumi, Erez; Lavy, Yotam; Wainstock, Tamar; Barrett, Chiya; Imtirat, Ahed; Sheiner, Eyal
Abstract: Objective: To examine whether smoking during pregnancy is correlated with long-term ophthalmic complications of the offspring. Study design: A population-based cohort analysis was performed comparing all deliveries of mothers who reported smoking during pregnancy and non-smoking mothers between 1991 and 2014 at a single tertiary medical center. Hospitalizations of the offspring up to the age of 18 years involving ophthalmic morbidities were evaluated according to a predefined set of ICD-9 codes. A Kaplan-Meier curve was used to compare cumulative hospitalization rate in exposed and unexposed offspring and a Cox proportional hazards model was used to control for confounders. Results: During the study period, 243, 680 deliveries met the inclusion criteria. Of them, 2965 (1.2%) were children of smoking mothers. Ophthalmic-related hospitalizations were significantly higher in children born to smoking mothers, as compared with the non-smoking group (1.4% vs. 0.1%, p < 0.01). Specifically, these hospitalizations were due to higher rates of visual disturbance rate and ophthalmic infections. The Kaplan-Meier curve demonstrated a significant higher cumulative incidence of ophthalmic-related hospitalizations in the smoking group (log rank p < 0.001). Using a Cox proportional hazards model, controlling for potential confounders, maternal tobacco use was found to be independently associated with long-term ophthalmic morbidity of the offspring (adjusted HR = 1.51, CI 1.11–2.04). Conclusion: Maternal smoking during pregnancy is an independent risk factor for long-term ophthalmic morbidity of the offspring. These results are in line with many recent studies that strongly support maternal smoking cessation during pregnancy due to high offspring morbidity risk. Highlights: Smoking during pregnancy is correlated with ophthalmic morbidity of the offspring. The effects of smoking during pregnancy on the offspring are long-term. The main contributors infections and visual disturbance